3D Lattice‐Matching Layered Hydroxide Heterostructure with Improved Interfacial Charge Transfer and Ion Diffusion for High Energy Density Supercapacitor. Issue 14 (27th June 2021) - Liu, Huanji; Zhu, Juncheng; Tian, Dan; Carvalho, Rodrigo; Shi, Zhicheng; Cai, Zhao; Chang, Xinghua; Araujo, Carlos Moyses; Zhou, Yu; Zhu, Jiliang
Abstract: The electrochemical charge storage mostly relies on the electrical properties of complex interfaces and electrode materials as well as the dynamic ions diffusion in the electrolytes. Nickel‐cobalt layered double hydroxides (LDHs) with tunable chemical composition are promising for electrochemical supercapacitors, where the theoretical performance could be up to 3000 F g −1 . However, the experimental performances of NiCo‐LDHs are still limited by low charge transfer rate and slow dynamic ions diffusion. Here, a 3D lattice matching Ni0.85 Co0.15 (OH)2 @α‐Co(OH)2 heterostructure is epitaxially grown. The experimental results and theoretical calculation confirm that such a 3D heterostructure could improve charge transfer abilities and accelerated ions diffusion. The specific capacitance of 2480 F g −1 and retained 71% of the initial capacitance at high current density of 30 A g −1 have been achieved by optimal Co(OH)2 amount of 20 mg (NCC‐20). Asymmetric button devices and soft‐pack devices have been demonstrated with exceptional energy densities of 69.2 and 65.7 Wh kg −1 at power densities of 0.79 and 0.78 kW kg −1, and maintained 88% and 80% initial capacitance under 10 000 cycles, respectively. The general design principles clearly demonstrate the importance of electrochemical interface and dynamic process, paving the way to push forward the application capability of electrochemical devices. Abstract : A 3D Ni0.85 Co0.15 (OH)2 @α‐Co(OH)2 heterostructure is designed with improved charge transfer and fast reaction dynamics, reaching theoretical limitation performance of 2480 F g −1 at 1 A g −1 . The asymmetric button and soft‐pack devices show exceptional energy densities of 69.2 and 65.7 Wh kg −1 at 0.79 and 0.78 kW kg −1 under 10 000 cycles.